Multimedia novels for internet generation (Net-Gen) readers in the cyberspace / Rosnidar Ain - Ain, Rosnidar (2015)
In the midst of rapid technological advance, a new era in literature writing has emerged. Wider network of Internet has given the opportunities to authors to become more prolific and creative in producing their work. In the virtual space, the number of authors grows and each one of them strives to grab the readers’ attention. Websites and social networking sites become the medium for authors to harness their creative mind through their writings. For writers who has envisioned becoming authors or writers who fail to establish themselves in the mainstream media, the Internet is perceived as a medium that is very easy for them to write. Nevertheless, with the impact of technological advances that covers almost all aspects of the public’s life, literary work is seen as not too distant from the conventional literature. The type of written material still resembles the printed ones. In fact, the use of multimedia is not fully utilized to produce literary work, which is different from the conventional literature materials. This study aims to analyze the novel as a genre in the Internet realm for the Internet generation (Net-Gen) through the utilization of multimedia in Malay literature. Through this study, the researcher will examine the novel genre, which is available on the Internet especially the novel in the form of multimedia, while investigating issues that might arise through observation, pilot survey and interviews conducted. Views and opinions obtained from this method will be used as data to form a model, which is a multimedia novel. This model will be tested on several respondents in order to collect data, which will be used as findings. Data, which are gathered, will be analyzed and a guideline about novel in the form of multimedia is created. Results from this research will benefit the field of literature in terms of literary knowledge in the form of multimedia that is distinguished from the conventional literature. With the advent of Internet, literary work must be more creative and not limited by the conventional literature alone but possesses its own distinct sets of disciplines